Supervised Exercise Therapy is Effective for Patients With Intermittent Claudication Regardless of Psychological Constructs. (March 2022) - Jansen, Sandra C.P.; Hoeks, Sanne E.; Nyklíček, Ivan; Scheltinga, Marc R.M.; Teijink, Joep A.W.; Rouwet, Ellen V.
Abstract : Objective: According to current guidelines, supervised exercise therapy (SET) is the treatment of choice for intermittent claudication (IC). Little is known about the potential consequences of psychological factors on the effectiveness of treatment. The aim of this study was to determine possible associations between a set of psychological constructs and treatment outcomes, and to investigate whether self efficacy increased after SET. Methods: This was a substudy of the ELECT Registry, a multicentre Dutch prospective cohort study in patients with IC receiving primary SET. A complete set of validated questionnaires scoring extraversion, neuroticism, conscientiousness, anxiety, depression, self control, optimism, and self efficacy was obtained in 237 patients (median age 69 years, 40% female). Anxiety and depression were dichotomised using established cutoff scores, whereas other scores were analysed as continuous measures. Multiple linear regression analyses determined possible associations between these independent variables and maximum and functional walking distances (MWD and FWD, respectively), Six Minute Walk Test (6MWT), and VascuQol-6 (dependent variables). Self efficacy during 12 months of SET was analysed using a linear mixed model. Results: Neuroticism and anxiety were associated with lower overall VascuQol-6 scores (estimate –1.35 points [standard error (SE) 0.57; p  = .018] and –1.98 points [SE 0.87, p  = .023], respectively). Optimism and self efficacy demonstrated higher overall 6MWT (5.92 m [SE 2.34; p  = .012] and 1.35 m [SE 0.42; p  = .001], respectively). Self control was associated with lower overall log MWD (–0.02 [SE 0.01; p  = .038] and log FWD (–0.02 [SE 0.01; p  = .080), whereas self efficacy had a higher overall log MWD (0.01 [SE 0.003; p  = .009]) and log FWD (0.01 [SE 0.003; p  = .011]). Depressive patients with IC demonstrated a greater improvement in 6MWT during follow up (17.56 m [SE 8.67; p  = .044]), but this small effect was not confirmed in sensitivity analysis. Self efficacy did not increase during follow up (0.12% [SE 0.49; p  = .080]). Conclusions: The beneficial effects of SET occur regardless of the psychological constructs, supporting current guidelines recommending a SET first strategy in each patient with IC.